IDENTIFICATION OF SECONDARY METABOLITE COMPOUNDS USING GC-MS IN METHANOL EXTRACTS OF KEISSI TUBERS (Stephania venosa (Blume) Spreng) - Salempa, Pince; Salnus, Subakir; Hasri (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Traditional medicinal plants are an important source of bioactive compounds that have the potential to be developed as raw materials for health products. One species used by the community in Mambi District, West Sulawesi, for cancer treatment is Belajang Keissi' (Stephania venosa (Blume) Spreng). This study aims to identify the secondary metabolites contained in the methanol extract of Belajang Keissi' tubers. The extraction process was carried out using the maceration method with methanol as the solvent, followed by qualitative phytochemical testing and compound profile analysis using GC-MS. The results of the phytochemical test showed that the methanol extract of Belajang Keissi' tubers contained alkaloids and flavonoids. Further GC-MS analysis revealed the presence of several dominant compounds, namely 9,12-octadecadienoic acid (Z,Z)-, methyl ester; trans-13-octadecenoic acid, methyl ester; methyl stearate; 6H-dibenzo[a,g]quinolizine, 5,8,13,13a-tetrahydro-2,3,9,10-tetramethoxy-; and (±)-2,3,3′,4′-tetramethoxy-α-methyl-5-(prop-1-enyl)stilbene. These findings indicate that Belajang Keissi tubers have potential as a source of bioactive compounds that can support the development of traditional medicines based on natural ingredients.